DAMPAK MEDIA SOSIAL TERHADAP PERILAKU ANAK DI ERA DIGITAL - Yanda, Mutiara; Renita Winarwan; Tin Rustini (Cahaya Ilmu Bangsa Institute, 2024)
Social media has become a significant part of children’s lives in the digital era, influencing various behavioral aspects, including communication patterns, self- perception, and social interactions. On one hand, platforms like Instagram and YouTube offer educational content that can broaden knowledge. However, excessive usage risks hindering children’s psychological and social development, especially in face-to-face communication skills and emotional management. Parental and educational guidance is essential in encouraging responsible social media use, helping children balance digital interactions with real-world social relationships. Through a collaborative approach, children are expected to adapt to technology positively while still cultivating essential social skills.